Tahap kesedaran terhadap tanggungjawab sosial korporat (CSR) dalam kalangan staf di organisasi korporat di Malaysia - Abdullah, Syahrina; Mohamad, Armanurah; Mahat, Nor Idayu (2013)
Corporate Social Responsibility (CSR) concept has been increasingly discussed as a hottest topic nowadays. CSR or Corporate Social Responsibility becomes an important issues and topics in the current national development agenda.In Malaysia, many efforts have been taken seriously by the government to ensure the CSR activities are involved by all level of community.This paper 14611 discuss the level of awareness of the CSR among the employees of corporate organizations in Malaysia.Based on past survey, many people agreed most of the corporate bodies only focus on company's profit.The issue to be discussed is whether staff of corporate organization aware the importance of CSR to the community and the environment. Study of 3 1 staff in the corporate organization's found that the level of awareness is high (mean =4.01) with standard deviation (sd = 0.65).This study will also discuss the implications for each dimension of CSR awareness to corporate organizations in Malaysia.